An investigation into prepositions in textbooks of english 10, 11, 12 at high schools in viet nam - Đặng Thị Hồng Hiệp (2015)
Prepositions are one of the important parts in learning English. Learners find it difficult to learn prepositions because of their variety. This thesis aims to investigate the prepositions in textbooks of English 10, 11, 12 in Viet Nam. By doing this research, I would like to study the prepositions which Vietnamese students learn at high school. 49 prepositions in 2195 sentences in the textbooks were collected. Besides, 10 teachers of English and 599 students at Nguyen Tat Thanh Gifted High School were also under survey to find out the difficulties in teaching and learning prepositions in Kon Tum City. The data were interpreted qualitatively and quantitatively. The prepositions were listed and grouped due to their semantic meanings and usages. They are: prepositions in collocations, prepositions in phrasal verbs and idioms, spatial prepositions, prepositions of time, prepositions of direction and path and prepositions in other uses. Moreover, we could understand some difficulties that teachers and students in Viet Nam may encounter when teaching and learning English. And then some solutions to the problems can be also raised to improve the teaching and learning English prepositions in Viet Nam.